(untitled) (Journal of Educational Sciences, 2024)
The problems of developing the ability to correctly pronounce sounds in connection with their language impairments in children is one of the pressing problems of special pedagogy. The article provides a review of the works of domestic and foreign scientists with a theoretical analysis of the stages of sound production through speech therapy work. A review of teaching methods for preschool children with special educational needs in distance learning was carried out. The updated methodology allows you to build a high-quality education and adapt to children’s environment, building equal relationships with others in society. 20 pupils of the special kindergarten “Akbota” and the speech therapy center “Speech Therapy Center” of the education department of the Aktobe region (10 children from each institution) took part in the experiment to test the methodology. For the study, permission and consent were taken from the children’s parents. The “World of Sounds” program was developed to develop readiness to use distance learning technologies to work with children. The experimental study consisted of 3 stages - diagnostic, formative and control stages. The mobile applications “Literate Child” and “World of Sounds” have been tested. The effectiveness of the updated technique has been demonstrated. Keywords: distance learning technology, children with special educational needs, preschool children, speech therapy, speech disorders.